2020
DOI: 10.4055/cios19127
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects and Complications of Pedicle Screw Augmentation with Bone Cement: Comparison of Fenestrated Screw Augmentation and Vertebroplasty Augmentation

Abstract: Spine surgery is increasing in frequency in the elderly population with osteoporosis along with the increased life expectancy. In addition to osteoporosis, deformities that demand rigid fixation are frequently observed in elderly patients. However, it is not easy to achieve enough fixation strength even with a pedicle screw system in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…It is well known that spinal instrumentation failures occur more often in osteoporotic spines. 18 , 19 In the case of posterior fixation with pedicle screws, failure is a result of decreased fixation strength in poor bone quality. 20 This insufficient fixation leads to increased instrument failure, such as screw pullout and loosening, warranting revision surgery that can lead to additional complications.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that spinal instrumentation failures occur more often in osteoporotic spines. 18 , 19 In the case of posterior fixation with pedicle screws, failure is a result of decreased fixation strength in poor bone quality. 20 This insufficient fixation leads to increased instrument failure, such as screw pullout and loosening, warranting revision surgery that can lead to additional complications.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most common indication of VP is an osteoporotic vertebral compression fracture that has failed conservative treatment [ 9 , 17 ]. Moreover, bone cement augmentation of the pedicle screws has been increasingly used to decrease the incidence of screw loosening in osteoporotic patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In theory, cement, as a bone adhesive, can rmly connect the implant material and bone to enhance its rmness. In recent years, many scholars and doctors carried out biomechanical and clinical research on the use of augmented-cement pedicle screws; They found that these screws could improve the stability and reliability of internal xation in patients with osteoporosis [20][21][22]. When we used the xation of cement-augmented pedicle screw, the bone-screw interface was transformed into the bone-cementscrew interface, and the screw and cement were closely combined so as to overcome the defect that the bone-screw interface was not rmly connected, resulting in the pulling out of the screw.…”
Section: Discussionmentioning
confidence: 99%